Implementation of Twin Digital Technology for Marinery Management and Conservation on Sulampua: An Innovative Approach in Blue Economy Optimization - Saumena, Fadly Yashari; Kamila, Alni Cahya (Research Parks Publishers, 2024)
This research explores the implementation of Digital Twin technology in tourism management and marine conservation in Sulawesi, Maluku and Papua (Sulampua) as an innovative approach to blue economy optimization. Digital Twin enables real-time digital modeling and simulation of the physical environment, improving the efficiency of natural resource management and tourism activities in a sustainable manner. The research method used Systematic Literature Review (SLR) to analyze related studies. The results show the great potential of this technology in supporting tourism management and marine conservation through real-time monitoring, prediction of environmental conditions, and data-driven decision-making. Challenges faced include limited technological infrastructure, lack of human resource capacity, resistance to adoption of new technologies, and coordination issues among stakeholders. Recommendations include increased investment in infrastructure, intensive training, and inclusive policy support to accelerate the adoption of Digital Twin technologies, supporting sustainable economic growth and marine ecosystem conservation in Sulampua.